Facing the center : toward an identity politics of one-to-one mentoring - Denny, Harry C. (Utah State University Press, 2010)
In the diversity of their clients as well as their professional and student staff, writing centers present a complicated set of relationships that inevitably affect the instruction they offer. In Facing the Center, Harry Denny unpacks the identity matrices that enrich teachable moments, and he explores the pedagogical dynamics and implications of identity within the writing center. The face of the writing center, be it mainstream or marginal, majority or miority, orthodox or subversive, always has implications for teaching and learning. Facing the Center will extend current research in writin.